Penyebaran Peradaban Islam di Asia Tenggara: The Spread of Islamic Civilization in Southeast Asia - Mawarni, Ummu Khairiyah; Arifi, Ahmad; Fatkhan, Muhammad (ITScience (Information Technology and Science), 2024)
This study uses a library research method, which includes analysis of scientific literature, books, and historical documents. Information is collected from relevant and credible works, including historical relics in the region. This study aims to describe the historical spread of Islam in Southeast Asia, explain the factors that influenced Islamization, and identify its impact on local communities' social, cultural, and political life. The study results show that Islam entered Southeast Asia through the role of Muslim traders from Arabia, Persia, and India who sailed through maritime trade routes. Sufis played an essential role in introducing Islam with a humanistic, moderate, and adaptive da'wah approach, which was adapted to local culture. Traces of Islamization can be seen in relics such as ancient tombs, classical Islamic books, and the tradition of Islamic boarding school education in Indonesia. Islam also developed rapidly in large kingdoms such as Samudra Pasai, Aceh Darussalam, Demak, and Mataram. Islamization in Southeast Asia lasted centuries, significantly transforming various aspects of people's lives. The region's social, cultural, and political systems are influenced by Islamic values, which introduced the principles of equality and justice amidst the previously dominant Hindu-Buddhist caste system. Educational legacies such as Islamic boarding schools have contributed significantly to spreading Islamic teachings and developing a generation of Muslim intellectuals who remain relevant today. Islam in Southeast Asia is also characterized by religious moderation, allowing Islamic teachings to coexist with local traditions and other religions. The region is now home to the largest Muslim populations in the world, with Indonesia, Malaysia, and Brunei Darussalam as examples of countries that have successfully integrated Islamic teachings into modern life.